If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 4c + -3 Reorder the terms: 21 = -3 + 4c Solving 21 = -3 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. 21 + -4c = -3 + 4c + -4c Combine like terms: 4c + -4c = 0 21 + -4c = -3 + 0 21 + -4c = -3 Add '-21' to each side of the equation. 21 + -21 + -4c = -3 + -21 Combine like terms: 21 + -21 = 0 0 + -4c = -3 + -21 -4c = -3 + -21 Combine like terms: -3 + -21 = -24 -4c = -24 Divide each side by '-4'. c = 6 Simplifying c = 6
| R-2+3r+8=3t-8 | | 1x*1/2x | | 175m-125m+47500=51250-200m | | 9e-6=12 | | 19-5x=10+4x+5x | | x^2-16x+y^2+6y-8=0 | | (X+3)(x+3)+(x-3)(x-3)-13=0 | | -7k+12=7+5k | | 5+4=x-7 | | -15=-10+p | | 20+4=6x | | 5x+3y=1100 | | 8x-2=9x+1 | | 3(x-2)=39 | | 3x+6=9x | | (2x+8)+x+x=180 | | 5n*1m=cjoule | | 10x-20=2(5x-4) | | x^3+12x^2+32x= | | 5x-2(x-4)=-3+5x-5 | | 5y-5-3y+2=0 | | 5n*1m= | | 3S+7=41+5S | | (2x-1)x(3x+4)= | | 4(x-6)+3x=11 | | 5+1+x=2+4 | | 4(x-7)+6=2x-10 | | 15x-4=50x+24 | | 0.5x-0.2(12-2x)=-0.1(x-6) | | 19x+16y=17 | | -4x-9=-2x-1 | | y=kx^2+8x+5 |